RELATIONSHIP OF BEHAVIORAL RISK FACTORS FOR CARDIOVASCULAR DISEASES AND ARTERIAL STIFFNESS IN WOMEN OF DIFFERENT AGE GROUPS WITH MEDICAL EDUCATION - O. S. Ivanova; E. Y. Maychuk; I. V. Voevodina (Евразийский Кардиологический Журнал, 2020)
Objective: to study the relationship of behavioral RF of CVD with arterial stiffness and daily dynamics of central aortic pressure in women of different age groups.Materials and methods: 161 women were examined, which were divided into 3 groups: 1st group – 52 young women from 18 to 30 years old (23.8±5.3 years old); 2nd group – 54 women from 31 years old until menopause (41±5.9 years); Group 3 – 55 women in the postmenopausal period (55.4±5.8 years). All volunteers underwent questionnaires, anthropometry, the study of arterial stiffness with the Doppler method and the method of volume sphygmography, daily monitoring of blood pressure with an assessment of vascular stiffness and central aortic pressure.Results: the strongest relationship between smoking and arterial stiffness was detected in the 3rd group, with the number of cigarettes per day being more important. Moderate alcohol consumption in group 1 is associated with an increase in the rate of increase in blood pressure in the aorta (dp / dt) max (R = 0.35, p = 0.01) and an improvement in the daily dynamics of central and peripheral pressure. A strict limitation of the caloric content of the consumed products is associated with a decrease in the carotidfemoral velocity of the  cfSPV pulse wave (R = -0.2, p = 0.01) and an improvement in the characteristics of the reflected wave in all groups. Only in the 1st group, the use of 400 grams or more vegetables and fruits per day is associated with an improvement in rigidity. Low physical activity in the 3rd group is associated with an increase in the Weissler coefficient (R = 0.28, p = 0.04) and AASI (R = 0.29, p = 0.03).Conclusion: behavioral RF of CVDs are interrelated with various indicators of arterial stiffness and changes in central and peripheral pressure in women of different ages. The most significant indicators can be used as markers for the development of subclinical changes in the vascular wall in women, depending on their risk factors in order to start preventive measures in a timely manner.